Sea Surface Roughness Observed by High Resolution Radar - Li, Xiaofeng (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Changes in sea surface roughness are usually associated with a change in the sea surface wind field. This interaction has been exploited to measure sea surface wind speed by scatterometry. A number of features on the sea surface associated with changes in roughness can be observed by synthetic aperture radar (SAR) because of the change in Bragg backscatter of the radar signal by damping of the resonant ocean capillary waves. With various radar frequencies, resolutions, and modes of polarization, sea surface features have been analyzed in numerous campaigns, bringing various datasets together, thus allowing for new insights into small-scale processes at a larger areal coverage. This Special Issue aims at investigating sea surface features detected by high spatial resolution radar systems, such as SAR.